ENHANCING PARENTAL INVOLVEMENT IN EDUCATION: SCHOOL MANAGEMENT STRATEGIES FOR BUILDING SCHOOL-HOME PARTNERSHIPS - Hasbullah Hasbullah (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research aims to identify effective school management strategies in enhancing parental involvement in education, with the ultimate goal of building a strong partnership between school and home. Parental involvement in education has long been recognized as having a significant positive impact on children's educational outcomes, including academic achievement and emotional well- being. The research method used was a literature review. The results show that effective communication between school and home is an important foundation in building an effective partnership. The use of modern technology such as mobile apps and other digital platforms was found to be helpful in facilitating such communication. In addition, the study also found that flexibility in engagement methods and providing rewards and recognition to parents significantly increased their level of participation. Accordingly, the study suggests the importance of education and training for parents, which not only enhances their ability to support their children academically but also enriches their involvement in the school community. In conclusion, supporting parental involvement requires a multifaceted and adaptive approach that recognizes and celebrates the contributions of each parent.